Qualitative Analysis of Recognition-based Graphical Password Authentication Schemes for Accessing the Cloud - K Gangadhara Rao; Vijayakumari Rodda; B Basaveswara Rao (Institute of Advanced Engineering and Science, 2017)
Cloud computing is increasingly becoming popular as many enterprise applications and data are moving into cloud platforms. However, a major barrier for cloud application is real and perceived lack of security. There are many security mechanisms exercised to utilize cloud services. Amongst them the prominent and primitive security mechanism is the Authentication System. Traditional text based passwords are susceptible to threats. Tough passwords are hard to recall and easily recalled passwords are simple and predictable. Graphical passwords are introduced as the better alternative. Two types of graphical passwords are there – recall based and recognition based. This research reviews several Recognition-Based Graphical Password methods and analyses their security based on the estimation criteria. Moreover, the research defines a metric called a 14-point scale that would make it possible for the qualitative analysis of the graphical passwords schemes.